2020
DOI: 10.1074/jbc.ra120.012706
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational folding stimulates programmed ribosomal frameshifting in the alphavirus structural polyprotein

Abstract: Viruses maximize their genetic coding capacity through a variety of biochemical mechanisms, including programmed ribosomal frameshifting (PRF), which facilitates the production of multiple proteins from a single mRNA transcript. PRF is typically stimulated by structural elements within the mRNA that generate mechanical tension between the transcript and ribosome. However, in this work, we show that the forces generated by the cotranslational folding of the nascent polypeptide chain can also enhance PRF. Using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 57 publications
4
53
0
Order By: Relevance
“…3). Consistent with previous findings (Harrington et al, 2020), our results show that the introduction of polar or charged side chains within a certain region of TM2 reduces -1PRF (V735-V746) while mutations that enhance the hydrophobicity of TM2 generally increase -1PRF (Fig. 3).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…3). Consistent with previous findings (Harrington et al, 2020), our results show that the introduction of polar or charged side chains within a certain region of TM2 reduces -1PRF (V735-V746) while mutations that enhance the hydrophobicity of TM2 generally increase -1PRF (Fig. 3).…”
Section: Resultssupporting
confidence: 92%
“…Our recent investigations of the impact of the nascent chain on -1PRF revealed that the mechanical force generated by the translocon-mediated membrane integration of the second TM domain within the E2 protein enhances ribosomal frameshifting in the SINV structural polyprotein (Harrington et al, 2020). Our DMS results reveal that ribosomal frameshifting is sensitive to a variety of mutations that alter the amino acid sequence within the portion of the nascent chain that has been translated at the point of frameshifting, including mutations to residues within the exit tunnel, between the exit tunnel and translocon, and within the second transmembrane domain of E2 (TM2, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed view of the cotranslational integration of three multispanning membrane proteins provided here shows that translocating nascent chains experience a distinct transition to a more hydrophobic environment at a distance of ~45 residues from the PTC, generating an oscillating force on the nascent chain that is ultimately transmitted to the PTC and varies in step with the appearance of each TMH in the vicinity of the SecYEG translocon channel. It seems likely that such oscillations can have multiple effects on the translation of membrane proteins, as recently demonstrated for ribosomal frameshifting ( Harrington et al, 2020 ), and may affect protein quality control ( Lakshminarayan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…The high-resolution view of the cotranslational integration of multi-spanning membrane proteins provided here show that translocating nascent chains experience a distinct transition to a more hydrophobic environment at a distance of ~45 residues from the PTC, generating an oscillating force on the nascent chain that is ultimately transmitted to the PTC and varies in step with the appearance of each TMH in the vicinity of the SecYEG translocon channel. It seems likely that such oscillations can have multiple effects on the translation of membrane proteins, as recently demonstrated for ribosomal frameshifting (25), and may affect protein quality control (26). Charged residues and membrane-interacting segments such as re-entrant loops and surface helices flanking a TMH can advance, delay, or attenuate its interaction with the translocon and surrounding lipid.…”
mentioning
confidence: 95%